2023
DOI: 10.1103/physrevapplied.20.014066
|View full text |Cite
|
Sign up to set email alerts
|

Laser Cooling in Semiconductor Heterojunctions by Extraction of Photogenerated Carriers

Paul Dalla Valle,
Marc Bescond,
Fabienne Michelini
et al.

Abstract: η rad φ in (E) Laser cooling of a semiconductor material, in which heat is extracted by emitting photons, requires a near-perfect external radiative efficiency. In this theoretical work, we propose a cooling system based on carrier extraction in a large gap reservoir. The electron-hole pairs generated in the material to be cooled are extracted in such a reservoir by absorbing phonons, then carrying a heat flux. With an analytical detailed balance model, we show that this concept is applicable even in materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These expressions are based on a three-dimensional (3D) description of the Landauer approach and use the 3D density-of-states in the reservoirs and the effective mass ( m *) approximation. They have been derived in a previous work . As J contact and P contact are proportional to m *, we use the limiting (smallest) effective mass for the implementation.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These expressions are based on a three-dimensional (3D) description of the Landauer approach and use the 3D density-of-states in the reservoirs and the effective mass ( m *) approximation. They have been derived in a previous work . As J contact and P contact are proportional to m *, we use the limiting (smallest) effective mass for the implementation.…”
Section: Modelmentioning
confidence: 99%
“…The radiative process causing optical refrigeration generally requires materials with radiative efficiency close to 1. , To overcome this requirement and based on the principle of evaporative cooling, we previously showed that extracting the photogenerated carriers into a larger bandgap reservoir generates cooling even with modest radiative efficiencies . Such a device requires a type I heterojunction, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%